The Role of Tax effort in the Flypaper effect Phenomenon and Its Implications for Fiscal Independence of Regencies/Cities in Java Island for the Period 2019-2024 - Pusparani Kirana Bagja Pusparani Kirana; Ken Paramitha Aryana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the flypaper effect phenomenon in regency/city governments in Java Island and to examine the role of tax effort in the relationship between the flypaper effect and fiscal independence. This study uses a quantitative approach with panel data from 113 regencies/cities in Java Island during 2019-2024, resulting in 678 observations. The data consist of Regional Expenditure, Local Own-Source Revenue, Intergovernmental Transfer Funds, Flypaper Effect, Tax Effort, and Fiscal Independence. The analytical method is panel data regression using the Fixed Effect Model and Moderated Regression Analysis. The results show that Local Own-Source Revenue and Intergovernmental Transfer Funds have a positive and significant effect on Regional Expenditure. The coefficient of Intergovernmental Transfer Funds is greater than that of Local Own-Source Revenue, indicating the occurrence of the flypaper effect. Regional testing also shows that 80 of 113 regencies/cities experience the flypaper effect. Furthermore, the flypaper effect has a negative and significant effect on fiscal independence. Tax effort has a positive and significant direct effect on fiscal independence and significantly moderates the relationship between the flypaper effect and fiscal independence. These findings indicate that the strengthening of local tax capacity remains important, but fiscal dependence on transfer funds must also be controlled through more performance-oriented transfer policies and sustainable optimization of local revenue.